Injury prevention strategies specific to pre-elite athletes competing in Olympic and professional sports - A systematic review - Smyth, E. A.; Newman, P.; Waddington, G.; Weissensteiner, J. R.; Drew, M. K. (Journal of Science and Medicine in Sport, 2019)
Objectives: To describe and evaluate injury prevention interventions for pre-elite athletes who compete in an Olympic or professional sport. Design: Systematic review. Methods: This review was prospectively registered (PROSPERO CRD42017065083) and a systematic electronic search was conducted in May 2017. The following inclusion criteria were applied: (1) studies including and analysing data specific to pre-elite athletes (determined by the T3/T4 levels of the FTEM model); (2) featured injury prevention interventions; (3) provided sufficient data related to injury such that the effect can be analysed e.g. injury rates, incidence, prevalence, injury rate ratios; (4) featured randomised and non-randomised controlled trials or prospective cohorts. Results: A total of 13,480 articles were retrieved with 121 titles identified and 11 studies satisfying the inclusion criteria. No studies demonstrated a low risk of bias. Four different interventions were identified: exercise (n = 7, 64%), psychological (n = 2, 18%), equipment (n = 1, 9%), nutrition (n = 1, 9%). Of the seven exercise interventions, four showed a protective effect and three found no significant effect, providing conflicting evidence. Caution is advised due to high risk of bias, low intervention reporting and minimal evidence for implementation planning in all seven studies. Conclusions: There is limited evidence from level 2 and 3 studies suggesting exercise and psychology interventions may prevent injury in pre-elite athletes. There is an absence of evidence to support the use of equipment and nutrition interventions in pre-elite athletes. There is a need for quality research designs confirming the clinical impact of existing injury prevention interventions for pre-elite athletes.